Influence of top-down and bottom-up manipulations on the R-BT065 subcluster of beta-proteobacteria, an abundant group in bacterioplankton of a freshwater reservoir - Simek, Karel; Hornák, Karel; Jezbera, Jan; Masín, Michal; Nedoma, Jirí; Gasol, Josep M; Schauer, Michael (Applied and environmental microbiology, 2005)
We studied the effects of nutrient availability and protistan grazing on bacterial dynamics and community composition (BCC) in different parts of the canyon-shaped Rímov reservoir (Czech Republic). The effects of protistan grazing on BCC were examined using a size fractionation approach. Water from the dam area with only bacteria (<0.8 microm), bacteria and heterotrophic nanoflagellates (<5 microm), or whole water were incubated in situ inside dialysis bags. Top-down or predator manipulations (size fractionation) were also combined with bottom-up or resource manipulations, i.e., transplantation of samples to the middle and upper inflow parts of the reservoir with increased phosphorus availability. Significant genotypic shifts in BCC occurred with transplantation as indicated by denaturing gradient gel electrophoresis. Using different probes for fluorescence in situ hybridization, we found that 10 to 50% of total bacteria were members of the phylogenetically small cluster of beta-proteobacteria (targeted with the probe R-BT065). These rod-shaped cells of very uniform size were vulnerable to predation but very fast growing and responded markedly to the different experimental manipulations. In all the grazer-free treatments, the members of the R-BT065 cluster showed the highest net growth rates of all studied bacterial groups. Moreover, their relative abundance was highly correlated with bacterial bulk parameters and proportions of bacteria with high nucleic acid (HNA) content. In contrast, increasing protistan bacterivory yielded lower proportions of R-BT065-positive and HNA bacteria substituted by increasing proportions of the class Actinobacteria, which profited from the enhanced protistan bacterivory.
Keywords: Nucleic Acids; Animals; ekosystém; Fresh Water; Ecosystem; Betaproteobacteria; zvířata; Food Chain; potravní řetězec; plankton; Plankton; nukleové kyseliny; biomasa; sladká voda; Phosphorus; Biomass; fosfor; Eukaryota